Role of Nanotechnology for Design and Development of Cosmeceutical: Application in Makeup and Skin Care - Aziz, Zarith Asyikin Abdul; Mohd-Nasir, Hasmida; Ahmad, Akil; Mohd. Setapar, Siti Hamidah; Peng, Wong Lee; Chuo, Sing Chuong; Khatoon, Asma; Umar, Khalid; Yaqoob, Asim Ali; Mohamad Ibrahim, Mohamad Nasir (Frontiers in Chemistry, 2019)
Nanotechnology is an innovative area of science that includes the design, characterization, production and application of materials, devices and systems by controlling shape and size at the nanometer scale (1 to 100 nm). Nanotechnology incorporation in cosmetic formulation is considered as the hottest and emerging technology available. Cosmetic manufacturers use nanoscale size ingredients to provide better UV protection, deeper skin penetration, long-lasting effects, increased color, finish quality and many more. Micellar nanoparticles is one of the latest field applied in cosmetic products that becoming trending and widely commercialized in local and international markets. The ability of nanoemulsion system to form small micellar nanoparticles size with high surface area allowing to effectiveness of bioactive component transport onto the skin. Oil in water nanoemulsion is playing a major role as effective formulation in cosmetics such as make-up remover, facial cleanser, anti-ageing lotion, sun-screens and other water-based cosmetic formulations. The objective of this review is to critically discuss the properties, advantageous and mechanism of micellar nanoparticles formation in nanoemulsion system. Therefore, present article introduce and discuss the specific benefits of nanoemulsion system in forming micellar nanoparticles for cosmetic formulation which become major factors for further development of micellar-based cosmetic segments.